Abortion and international law - Kubacka, Anna (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Contrary to theses often repeated in public debate, abortion is not recognized as a human right under international law. International instruments recognize the right to life as the first and most fundamental right, without limitation clauses, and as a sine qua non for exercising other rights, such as health or privacy. Attempts to establish abortion as a basic human right rest mainly on "soft law": non-binding documents, standards, recommendations, and guides. The pro-abortion narrative today detaches abortion from the right to life, binding it instead to health or self-determination rights, excluding any link between terminating a pregnancy and the life of another human being. The chapter analyses, among others, the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the Convention on the Rights of the Child, the European Convention on Human Rights, and EU and UN activity on procreation.